A Schiff base derivative for effective treatment of diethylnitrosamine-induced liver cancer in vivo - Demirci, Selami; Dogan, Aysegul; Basak, Nese; Telci, Dilek; Dede, Bulent; Orhan, Cemal; Sahin, Fikrettin (Lippincott Williams & Wilkins, 2015)
Hepatocellular carcinoma is one of the most prevalent cancers, with a high morbidity rate, even in developed countries. In the present study, the curative effect of the Schiff base (SB) heterodinuclear copper(II) Mn(II) complex on diethylnitrosamine (DEN)-induced liver carcinoma was investigated. Hepatocarcinoma was initiated by an injection of DEN and promoted by phenobarbital (0.05%) in the diet. In addition, the potential nephrotoxicity of SB was evaluated in a cisplatin-induced nephrotoxicity model. Rats were administered the SB complex (1 and 2 mg/kg body weight/day) for 24 weeks, and cancer progression was investigated by macroscopic, histopathological, and western blot examinations. The administration of SB decreased the incidence and the number of hepatic nodules in a dose-dependent manner by regulating inflammation response and the apoptotic pathway. Western blot analyses from the livers of rats treated with SB after DEN induction showed significantly enhanced Bax and caspase-3 levels, with a marked decrease in the levels of Bcl-2, NF-kappa B p65 and cyclooxygenase (COX)-2. Results from the nephrotoxicity study showed that, whereas cisplatin increased serum urea nitrogen and creatinine levels, no increase in serum biochemical parameters was detected in SB-treated animals. Moreover, protein levels of NF-E2-related factor-2 (Nrf2) and heme oxygenase-1 were lower, whereas nuclear factor-kappa B (NF-kappa B p65) and activator protein-1 levels were higher in the kidneys of cisplatin-treated animals compared with that of the SB groups. Therefore, the SB complex could be an alternative chemotherapeutic option for liver cancer treatment once its safety in clinical applications has been examined. Copyright (C) 2015 Wolters Kluwer Health, Inc. All rights reserved.
Keywords: diethylnitrosamine; hepatocarcinogenesis; liver cancer; nephrotoxicity; Schiff base